Tata Laksana Diabetes Melitus Tipe 1 dengan Ketoasidos Diabetik pada Anak 7 Tahun dengan Sindrom Down dan Gizi Buruk di Rumah Sakit dengan Layanan Terbatas: Case Report - Padmita Utami, Ida Ayu; William Cheng; Ni Made Reditya Noviani (Lombok Medical Journal, 2024)
The incidence of children with Type-1 Diabetes Mellitus (T1DM) is increasing both worldwide and in Indonesia. The Indonesian Pediatric Society (IPS) recorded 1120 pediatric patient with T1DM in 2018. Potential complication of type 1 DM is Diabetic ketoacidosis (DKA). Diabetic ketoasidosis is a terminal condition in metabolic abnormalities caused by severe insulin deficiency. Patients with Down syndrome (DS) have an increased risk of developing autoimmune diseases such as Type 1 Diabetes Mellitus (T1DM). This is a rare case of a Down Syndrom patient with a clinical profile of severe malnutrition, which can lead to serious complication.